Implementation of Assertive Acceptance Commitment Therapy (AACT) in Schizophrenia With Violence at RSJD DR. Amino Gondohutomo Central Java Province - Diyan Yuli Wijayanti; Meidiana Dwidiyanti; Nur Intan Fitriani; Chika Ayu Tyara; Ibnu Foyas Hermanto (Jurnal Ners, 2025)
The risk of violent behavior is a problem that most often arises in schizophrenic. The inability to control emotions will lead to aggressive behavior both verbally and non-verbally directed at oneself, others and the surrounding environment. Assertive Acceptance Commitment Therapy (AACT) is one of the interventions that can be given by integrating Assertive Training (AT) and Acceptance and Commitment Therapy (ACT). AACT can provide skills for assertive behavior so that patients will be able to accept the problems experienced with adaptive behavior and have a commitment to maintain that behavior in all conditions. The purpose of this study was to apply and analyze the results of the AACT intervention in schizophrenic patients at risk of violent behavior. The method used in this research is a case study, namely research that aims to investigate an existing event or phenomenon. Data were analyzed by directly interpreting and describe the results of calculating the increase in the GAFR score and then explaining by using textual and discourse analysis. The results of this study showed that there was a significant improvement in the General Adaptive Function Response (GAFR) score after the AACT intervention was given. The average increase in GAFR score was 16,33 (intensive 2). It means that, all patients experience an increase in the ability of Adaptive Function Response. AACT can help schizophrenic patients with violence to have a more assertive behavior, accept the problem, their condition, and commit to maintaining adaptive behavior so that clients can control their anger.